DIMENSI PENGETAHUAN LOKAL PADA MITOS SUMBER AIR DI DUSUN BEJI KECAMATAN JOGOROTO KABUPATEN JOMBANG (Kajian Kearifan Lokal Jim Ife) - Mei, Farusia (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2021)
The purpose of this study is to gain local knowledge that belongs to the beji community. Local knowledge is derived from the adaptation of communities that have lived in an environment and in a given period of time. The study USES qualitative methods with an ethnographic approach with a view to describing and presenting data in a description of local knowledge that is closely related to community culture. The technique for collecting the data is to come directly to the research site and do an interview with the source. This study suggests that developed in the beji community, has local knowledge of the changing conditions of regional names, climate cycles, geography, sociography, and natural symbols that are very useful to everyday life.